Consumer Perceptions of Sustainable Products in the Digital Age: Analysis of the Influence of E-WOM and Transparency (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
In the digital age, consumer awareness of sustainable products has increased significantly. Recent research (2023-2025) shows that 84% of Indonesian consumers have used eco-friendly products, driven by a desire to preserve the earth. The purpose of this study is to analyze how digital information, particularly Electronic Word-of-Mouth (E-WOM), perceptions of sustainable packaging, and environmental concerns influence consumer perceptions and purchasing decisions in Indonesia. The proposed method is a quantitative approach using multiple linear regression analysis, preceded by classical assumption testing and instrument reliability testing. Key findings from the supporting literature indicate that E-WOM has a strong influence on purchase interest, even mediating the relationship between green marketing and purchase intention. In addition, product information transparency (ecological labels) is significant in increasing trust. The conclusion confirms that effective digital strategies must prioritize positive E-WOM communication and sustainability data transparency.